ANALISIS KELAYAKAN USAHA PENGOLAHAN IKAN SALAI DI KELURAHAN AIR DINGIN KECAMATAN BUKIT RAYA KOTA PEKANBARU PROVINSI RIAU (Studi Kasus Pada Usaha Ikan Salai Sedap Bakat) - Eka Marlena; Azharuddin M Amin (UIR Press, 2022)
This study aims to analyze the characteristics of entrepreneurs and smoked fish business profile; availability, acquisition, and use of raw materials and supporting materials for smoked fish processing business; non-financial business feasibility and financial feasibility of smoked fish processing business; and the sensitivity of the smoked fish processing business. The method used in this research was a case study in the processing business of